Contracting in medical equipment maintenance services: An empirical investigation - Tian Chan; Francis de Véricourt; Omar Besbes (European School of Management and Technology (ESMT), 2014)
Equipment manufacturers offer different types of maintenance service plans (MSPs) that delineate payment structures between equipment operators and maintenance service providers. These MSPs allocate risks differently and thus induce different kinds of incentives. A fundamental question, therefore, is how such structures impact service performance and the service chain value. We answer empirically this question. Our study is based on a unique panel data covering the sales and service records of over 700 diagnostic medical body scanners. By exploiting the presence of a standard warranty period, we overcome the key challenge of isolating the incentive effects of MSPs on service performance from the confounding effects of adverse selection. We found that moving an operator from a basic pay-per-service plan to a fixed-fee full-protection plan leads to both a reduction in reliability and an increase in service costs. We further show that the increase in cost is driven by both the operator and the service provider. Our results point to the presence of losses in service chain value in the maintenance of medical equipment, and provide the first evidence that a basic pay-per-service plan, where the risk of equipment failure is borne by the operator, can actually improve performance and costs.
urn:nbn:de:101:1-201409171648
Keywords: 650; maintenance repair; service contracting; co-production; empirical operations management; service chain value; healthcare industry